Analysis of Learning Outcome Indicator Completion through Verification of Concept Maps and Mind Maps in the Discovery Learning Model - Yunus, Muhammad; Islawati, Islawati; Auliah, Army (PT FORMOSA CENDEKIA GLOBAL, 2025)
A less systematic conceptual understanding can hinder the completion of student learning outcomes. This study aims to compare the verification of concept maps and mind maps in improving student understanding in the Discovery Learning model. The method used is descriptive comparative, with two experimental groups each using concept maps and mind maps. The research process includes pretest, intervention with verification, posttest, and student reflection. Data collection was carried out through learning outcome tests, assessment rubrics, and observations. The results of the study showed that concept maps support more systematic understanding, while mind maps are more effective in developing flexibility of thinking. The verification process plays a role in correcting students' conceptual errors. These findings provide insight for educators to adjust learning methods to improve learning outcomes.